Tren Rambut Sambung di Kalangan Perempuan Papua - Krimadi, Theresia; Paramita, Sinta (Kiwari, 2024)
The development of technology has given rise to various trends in Indonesia, one of which is the trend of hair extensions which is currently popular among Papuan women, because it can help them in giving the latest hairstyles. Hair extensions by weaving/braiding have become commonplace among Papuan women, because this has become part of the lifestyle of Papuan women and is inherent as a characteristic of Papuan women. This study uses a qualitative approach method, to find out more about the views of Papuan women who use hair extensions as a hairstyle. The study is supported by the theory of symbolic interaction, which is discussed in this theory related to the perception and self-concept of social society. The results of this study, according to Papuan women who use hair extensions, strongly agree with the impact of this trend, which initially they were less confident with short curly hair, but with hair extensions it helps them appear more confident. Hair extensions by braiding come from Arika, then adopted by Papuan women because they have the same hair type. Hair extensions are not an original culture or characteristic of women, so this has become a debate for Papuan women. Perkembangan teknologi memunculkan berbagai macam tren di Indonesia, salah satunya tren rambut sambung yang saat ini menjadi populer di kalangan perempuan Papua, karena bisa membantu mereka dalam memberikan gaya rambut terbaru. Rambut sambung dengan cara dianyam/kepang sudah menjadi hal yang biasa dikalangan perempuan Papua, dikarenakan hal ini telah menjadi bagian dari gaya hidup perempuan Papua dan melekat menjadi ciri khas perempuan Papua. Penelitian ini menggunakan metode pendekatan kualitatif, untuk mengetahui lebih dalam tentang pandangan perempuan Papua yang menggunakan rambut sambung sebagai gaya rambut. Penelitian didukung dengan teori interaksi simbolik, yang dipembahasan dalam teori ini terkait persepi dan konsep diri masyarakat sosial. Hasil dari penelitian ini, menurut perempuan Papua yang menggunakan rambut sambung, sangatlah setuju dengan dampak dari tren ini, yang awalnya mereka kurang percaya diri dengan rambut keriting pendek, namun dengan adanya rambut sambung membantu mereka tampil lebih percaya diri. Rambut sambung dengan cara dikepang ini berasal dari Arika, kemudian diadopsi oleh perempuan Papua dikarenakan memiliki kesamaan tipe rambut. Rambut sambung bukanlah budaya asli atau ciri khas perempuan, sehingga hal tersebut menjadi sebuah perdebatan bagi perempuan Papua.